Potassium tantalate niobate-doped friction nano-generator and preparation method thereof

By using a friction pair composed of a polyvinyl alcohol-spun film doped with potassium tantalum niobate and a perfluoroethylene propylene copolymer in a friction nanogenerator, the problems of vulnerability and high cost of existing TENG materials are solved, and high charge density and stable output performance are achieved.

CN120150544APending Publication Date: 2025-06-13YANTAI ADVANCED MATERIALS & GREEN MFG SHANDONG PROVINCIAL LAB +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510309964.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

In practical applications, existing friction nanogenerators have problems such as material vulnerability, low weather resistance, poor thermal stability, high cost and complex process, and it is difficult to develop TENG with high charge density.

Method used

TENG was prepared by electrospinning process by using a polyvinyl alcohol-doped film doped with potassium tantalum niobate as the friction sub-positive positive electrode, and combined with perfluoroethylene propylene copolymer as the friction sub-negative electrode.

Benefits of technology

TENG is achieved with high mechanical strength and excellent output performance. The output peak is reached within 10 to 30 seconds, the short circuit current and short circuit voltage are between 15 to 60μA and 600 to 1400V respectively, and the material cost is low and the preparation method is simple, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120150544A_ABST
    Figure CN120150544A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of friction nano-generators, and particularly relates to a friction nano-generator doped with potassium tantalate niobate and a preparation method, the nano-generator comprises a friction pair positive electrode and a friction pair negative electrode, the friction pair positive electrode is made of a polyvinyl alcohol spinning film doped with potassium tantalate niobate, and the friction pair negative electrode is made of a perfluoroethylene propylene polymer. A certain proportion of potassium tantalate niobate is added into a polyvinyl alcohol spinning solution with a certain concentration to prepare a spinning film, and the spinning film and a friction pair perfluorinated ethylene propylene copolymer form S-STENG. The nano generator not only has better mechanical strength, but also has better output performance. The potassium tantalate niobate is a high dielectric material, has high capacitance and strong electric field responsiveness, and can more effectively adsorb and store charges when rubbing with other materials. The KTN has high dielectric strength and can bear a stronger electric field without breakdown. This makes the TENG more stable at high voltage output.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of triboelectric nanogenerators, and particularly relates to a triboelectric nanogenerator doped with potassium tantalum niobate and a preparation method thereof. Background Art

[0002] The global energy demand is increasing day by day, and the consumption of traditional energy has caused a huge impact on the environment. In particular, the use of fossil fuels has triggered problems such as climate change and environmental pollution. Therefore, it is very important to find clean and sustainable energy sources. A triboelectric nanogenerator (TENG) is a device based on the coupling principle of triboelectrification and electrostatic induction. As a new type of energy conversion technology, it can convert mechanical energy such as the movement and friction of the surrounding environment into electrical energy, and has broad prospects. The performance of TENG depends to a large extent on the materials used. In order to improve the electrical energy conversion efficiency and stability of triboelectric nanogenerators, a large number of explorations and innovations have been carried out in material modification, including surface modification, nanocoating technology, surface charge regulation, etc. Specific surface modifications include anodization, silicone resin coating, plasma treatment, etc.

[0003] However, TENGs based on the above methods also have some disadvantages in practical applications. For example, the surface of anodized materials is easily damaged and limited by the types of metals; the bonding force between silicone resin coatings and some substrate materials is low, and the coating materials are prone to peeling off during the friction process, with disadvantages such as low weather resistance and poor thermal stability; the effect of plasma treatment is unstable and the treatment is uneven. There are generally problems such as high cost and complex processes. In addition, the above modification methods are relatively complex and the cost is relatively high. TENG has high requirements for output. Developing TENGs with high charge density is of great significance because the output energy is proportional to the square of the charge density. Therefore, how to design TENGs that meet actual requirements still faces severe challenges. Summary of the Invention

[0004] The present invention discloses a triboelectric nanogenerator doped with potassium tantalum niobate and a preparation method thereof. A certain proportion of potassium tantalum niobate is added to a spinning solution of polyvinyl alcohol with a certain concentration to form a spinning film, which is combined with a friction pair of perfluoroethylene propylene copolymer to form an S-STENG. This nanogenerator not only has good mechanical strength but also has good output performance. Potassium tantalum niobate is a high-dielectric material with high capacitance and strong electric field responsiveness. When they rub against other materials, they can more effectively adsorb and store charges. KTN has a high dielectric strength and can withstand a stronger electric field without breakdown. This makes the TENG more stable during high-voltage output.

[0005] To achieve the above object, the technical solution of the present invention is:

[0006] A triboelectric nanogenerator doped with potassium tantalum niobate, comprising a positive friction pair and a negative friction pair. The positive friction pair is made of a polyvinyl alcohol (PVA) spinning film doped with potassium tantalum niobate (KTN), and the negative friction pair is made of a perfluoroethylene propylene polymer (FEP).

[0007] A preparation method of a triboelectric nanogenerator doped with potassium tantalum niobate, including a first preparation method of a polyvinyl alcohol (PVA) spinning film doped with potassium tantalum niobate (KTN), comprising the following steps: First, dissolve polyvinyl alcohol (PVA) in deionized water at 80 °C, heat and stir to obtain a polyvinyl alcohol (PVA) aqueous solution; then synthesize potassium tantalum niobate (KTN) by a hydrothermal method, and add potassium tantalum niobate (KTN) to the polyvinyl alcohol (PVA) aqueous solution according to a certain mass fraction to obtain an electrospinning solution, and obtain a polyvinyl alcohol (PVA) spinning film doped with potassium tantalum niobate (KTN) through electrospinning.

[0008] Preferably, the first preparation method includes the following specific steps: Heat a certain amount of deionized water to 80 °C, add a certain mass of polyvinyl alcohol (PVA) powder to make a polyvinyl alcohol (PVA) aqueous solution with a mass fraction of 6% - 15%; weigh a certain mass of potassium tantalum niobate powder, add it to a certain amount of polyvinyl alcohol aqueous solution, and magnetically stir for 1 h to make a polyvinyl alcohol spinning solution with a mass fraction of 0.4% - 1.6% potassium tantalum niobate; use the electrospinning process to make a polyvinyl alcohol spinning film doped with potassium tantalum niobate.

[0009] Preferably, in the first preparation method, the mass ratio of deionized water, polyvinyl alcohol (PVA), and potassium tantalum niobate (KTN) is 60 - 90:6 - 10:0.06 - 0.3.

[0010] Preferably, in the electrospinning process, the applied voltage of the electrospinning solution is 10 - 20 kV, and the feeding rate is 0.1 - 0.3 mL h -1 , and the spinning distance from the receiving plate is 10 - 15 cm.

[0011] Preferably, it also includes a second preparation method for manufacturing the positive friction pair and the negative friction pair, specifically: Use a 5 cm × 5 cm PVA / KTN spinning film (a polyvinyl alcohol spinning film doped with potassium tantalum niobate) as the positive friction pair, and a 5 cm × 5 cm perfluoroethylene propylene polymer (FEP) as the negative friction pair, and assemble a triboelectric nanogenerator through the positive friction pair and the negative friction pair.

[0012] Preferably, it further includes Preparation Method 3 for preparing potassium tantalum niobate (KTN). Specifically: First, a certain mass of flaky solid potassium hydroxide (KOH) is dissolved in deionized water and stirred to prepare a 5-10 mol / L potassium hydroxide (KOH) solution. Weigh Ta 2 O 5 and Nb 2 O 5 in a molar ratio of 2-6:3-8 and add them to the potassium hydroxide (KOH) solution to obtain a potassium hydroxide (KOH) mixed solution; add 0.1-0.5 g of polyvinyl alcohol (PVA) surfactant to the potassium hydroxide (KOH) mixed solution; use a magnetic stirrer to stir the above-obtained mixed solution for 1-3 hours, then pour the mixed solution into the polytetrafluoroethylene inner liner of a hydrothermal reaction kettle and react at 100-350 °C for 10-20 hours; after the reaction stops, let it cool naturally to room temperature, filter and wash with deionized water and absolute ethanol to obtain potassium tantalum niobate (KTN) precipitate, and then dry it for 2 hours to obtain potassium tantalum niobate (KTN) powder.

[0013] Preferably, in Preparation Method 3, the mass fraction ratio of the potassium hydroxide (KOH) solution, the mixture of Ta 2 O 5 and Nb 2 O 5 and the polyvinyl alcohol (PVA) surfactant is: 90-110:1:0.1-0.5.

[0014] Preferably, in Preparation Method 3, the particle sizes of Ta 2 O 5 and Nb 2 O 5 are about 5-10 μm and 1-10 μm respectively.

[0015] Preferably, in Preparation Method 1 and Preparation Method 3, the polyvinyl alcohol is one of polyvinyl alcohol 2699, polyvinyl alcohol 1788, polyvinyl alcohol 1799, polyvinyl alcohol 2099, and polyvinyl alcohol 2488.

[0016] The beneficial effects of a triboelectric nanogenerator doped with potassium tantalum niobate and its preparation method of the present invention are as follows:

[0017] (1) The raw materials required by the present invention have low costs, the preparation method is simple, and it is easy to mass-produce. The electrospun membrane provided by the present invention is green and pollution-free.

[0018] (2) The electrospinning doped TENG provided by the present invention has excellent triboelectric performance, reaches the output peak within 10-30 s after operation, and the short-circuit current and short-circuit voltage are about 15-60 μA and 600-1400 V respectively.

[0019] (3) In the present invention, the electrospun membrane has a high specific surface area, which can increase the frictional contact area of the material, thereby enhancing the triboelectric effect of the material.

[0020] (4) In the present invention, KTN has high dielectric properties. After doping, a high-polarity interface can be formed. The increase in the dielectric constant will increase the charge density, thereby improving the output. Description of the Drawings

[0021] Figure 1 Short-circuit current and open-circuit voltage of the electrospun modified doped TENG provided in Example 1;

[0022] Figure 2 SEM characterization of the electrospun modified doped TENG provided in Example 1;

[0023] Figure 3 Short-circuit current and open-circuit voltage of the electrospun modified doped TENG provided in Example 2;

[0024] Figure 4 SEM characterization of the electrospun modified doped TENG provided in Example 2;

[0025] Figure 5 Short-circuit current and open-circuit voltage of the electrospun modified doped TENG provided in Example 3;

[0026] Figure 6 SEM characterization of the electrospun modified doped TENG provided in Example 3. Detailed Description of the Invention

[0027] The following description is only for the preferred embodiments of the present invention and is not intended to limit the protection scope of the present invention. Any modifications, equivalent replacements, and improvements made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.

[0028] The following embodiments can be understood as separately representing a part of the local structure or method of the present invention, or can also be understood as the embodiments combined with each other to explain the connotation of the structure or method of a larger scope of the present invention.

[0029] Example 1

[0030] First, a certain mass of flaky solid potassium hydroxide (KOH) is dissolved in deionized water and stirred to prepare a 6 mol / L KOH solution. Weigh 1 g of Ta with a molar ratio of 2:3 2 O 5 and Nb 2 O 5It was added to 94 g of 6 mol / L KOH solution, and then 0.1 g of polyvinyl alcohol (PVA) surfactant was added to the KOH mixed solution. After the KOH mixed solution was stirred for 1 hour with a magnetic stirrer, the mixed solution was poured into a polytetrafluoroethylene inner liner, fixed in a hydrothermal reaction kettle, and reacted at 150 °C for 10 hours. After the reaction stopped, it was allowed to cool naturally to room temperature, and the KTN precipitate was obtained by suction filtration and washing with deionized water and absolute ethanol, and then dried for 2 hours to obtain KTN powder.

[0031] 92 g of deionized water was heated to 80 °C, and 8 g of polyvinyl alcohol 1788 powder was added to prepare a PVA solution with a mass fraction of 8%. 0.032 g of KTN powder was weighed and added to 8 g of 8% PVA solution, and magnetically stirred for 1 h to prepare a PVA spinning solution with a KTN mass fraction of 0.4% to obtain a KOH mixed solution. The fiber membrane was deposited on a copper tape by electrospinning technology. The applied voltage of the electrospinning solution was 10 kV, and the feeding rate was 0.1 mL / h -1 , the spinning distance was 8 cm, and a spinning membrane doped with KTN in PVA was prepared. A 5 cm × 5 cm spinning membrane was used as the positive friction pair, and a 5 cm × 5 cm fluorinated ethylene propylene polymer (FEP) was used as the negative friction pair to assemble a TENG.

[0032] The ISC data of the sample at a filter frequency of 100 kHz was measured using an SR570 low-noise current preamplifier (Stanford Research Systems, USA), and the sampling rate was set at 100000 Hz. The output voltage of the PT-TENG was measured using a three-series mixed-domain oscilloscope (Tektronix), and the resistance was 100 MΩ. A field emission scanning electron microscope (SEM) was also used to characterize the microscopic morphology of the surface of the sample membrane. The short-circuit current and open-circuit voltage of Example 1 can be obtained as Figure 1 shown. As can be seen from the figure, the short-circuit current and open-circuit voltage of Example 1 were 22 μA and 800 V respectively, showing a significant improvement compared with the output of the PVA spinning membrane. As Figure 2 shown, through SEM characterization, it can be obtained that the surface of the sample in Example 1 has uniform spinning thickness and regular arrangement, indicating that it is suitable as a TENG.

[0033] Example 2

[0034] First, a certain mass of flaky solid potassium hydroxide (KOH) was dissolved in deionized water and stirred to prepare an 8 mol / L KOH solution. 1 g of Ta with a molar ratio of 3:5 was weighed 2 O 5 and Nb 2 O 5It was added to 101 g of 8 mol / L KOH solution to obtain a KOH mixed solution. 0.2 g of polyvinyl alcohol (PVA) surfactant was added to the KOH mixed solution. The above-obtained mixed solution was stirred with a magnetic stirrer for 2 hours, then the mixed solution was poured into a polytetrafluoroethylene inner liner, fixed in a hydrothermal reaction kettle, and reacted at 200 °C for 15 hours. After the reaction stopped, it was allowed to cool naturally to room temperature, and the KTN precipitate was obtained by suction filtration and washing with deionized water and absolute ethanol, and then dried for 2 hours to obtain KTN powder.

[0035] 94 g of water was heated to 80 °C, and 6 g of polyvinyl alcohol 2699 powder was added to make a PVA solution with a mass fraction of 6%. 0.056 g of KTN powder was weighed and added to 8 g of 6% PVA solution, and magnetically stirred for 1 h to make a PVA spinning solution with a KTN mass fraction of 0.7%. The fiber membrane was deposited on the copper tape by electrospinning technology. The applied voltage of the electrospinning solution was 15 kV, and the feeding rate was 0.2 mL / h -1 , the spinning distance was 10 cm, and a PVA-doped KTN membrane was prepared. A 5 cm × 5 cm PVA / KTN spinning membrane was used as the positive friction pair, and a 5 cm × 5 cm fluorinated ethylene propylene polymer (FEP) was used as the negative friction pair to assemble a TENG.

[0036] The SR570 low-noise current preamplifier (Stanford Research Systems, USA) was used to measure the ISC data of the sample at a filter frequency of 100 kHz, and the sampling rate was set at 100000 Hz. A three-series mixed-domain oscilloscope (Tektronix) was used to measure the output voltage of the PT-TENG, and the resistance was 100 MΩ. A field emission scanning electron microscope (SEM) was also used to characterize the microscopic morphology of the surface of the sample membrane. The short-circuit current and open-circuit voltage of Example 2 can be obtained as Figure 3 shown. As can be seen from the figure, the short-circuit current and open-circuit voltage of Example 2 were 32 μA and 1150 V respectively, which were both doubled compared with the output of the PVA spinning membrane. As Figure 4 shown, through SEM characterization, it can be obtained that the surface of the sample has uniform spinning thickness and regular arrangement, indicating that it is suitable as a TENG.

[0037] Example 3

[0038] First, a certain mass of flaky solid potassium hydroxide (KOH) was dissolved in deionized water and stirred to prepare a 9 mol / L KOH solution. 1 g of Ta with a molar ratio of 4:7 was weighed 2 O 5 and Nb 2 O 5It was added to 105 g of 9 mol / L KOH solution to obtain a KOH mixed solution. 0.25 g of polyvinyl alcohol (PVA) surfactant was added to the KOH mixed solution. After stirring the above-obtained mixed solution with a magnetic stirrer for 1 hour, the mixed solution was poured into a polytetrafluoroethylene inner liner, fixed in a hydrothermal reaction kettle, and reacted at 250 °C for 18 hours. After the reaction stopped, it was allowed to cool naturally to room temperature, and the KTN precipitate was obtained by suction filtration and washing with deionized water and absolute ethanol, and then dried for 2 hours to obtain KTN powder.

[0039] 88 g of water was heated to 80 °C, and 12 g of polyvinyl alcohol 2099 powder was added to prepare a 12% PVA solution by mass fraction. 0.105 g of KTN powder was weighed and added to 8 g of 12% PVA solution, and magnetically stirred for 1 h to prepare a PVA spinning solution with a KTN mass fraction of 1.3%. The fiber membrane was deposited on a copper tape by electrospinning technology. The applied voltage of the electrospinning solution was 18 kV, and the feeding rate was 0.3 mL / h -1 , the spinning distance was 13 cm, and a PVA-doped KTN membrane was prepared. A 5 cm × 5 cm PVA / KTN spinning membrane was used as the positive friction pair, and a 5 cm × 5 cm fluorinated ethylene propylene polymer (FEP) was used as the negative friction pair to assemble a TENG.

[0040] The SR570 low-noise current preamplifier (Stanford Research Systems, USA) was used to measure the ISC data of the sample at a filter frequency of 100 kHz, and the sampling rate was set at 100000 Hz. A three-series mixed-domain oscilloscope (Tektronix) was used to measure the output voltage of the PT-TENG with a resistance of 100 MΩ. A field emission scanning electron microscope (SEM) was also used to characterize the microscopic morphology of the surface of the sample membrane. The short-circuit current and open-circuit voltage of Example 3 can be obtained as Figure 5 shown. As can be seen from the figure, the short-circuit current and open-circuit voltage of Example 3 were 32 μA and 1150 V respectively, which were 1.5 times higher than those of the PVA spinning membrane. As Figure 6 shown, through SEM characterization, it can be obtained that on the surface of the example, some spinning fibers adhered to each other and were unevenly distributed, but the output was not reduced, indicating that it was suitable as a TENG.

[0041] Example 4

[0042] A triboelectric nanogenerator doped with potassium tantalum niobate, comprising a positive friction pair and a negative friction pair. The positive friction pair is made of a polyvinyl alcohol (PVA) spinning membrane doped with potassium tantalum niobate (KTN), and the negative friction pair is made of a fluorinated ethylene propylene polymer (FEP).

[0043] Example 5

[0044] A preparation method of a triboelectric nanogenerator doped with potassium tantalum niobate, including a first preparation method of a polyvinyl alcohol (PVA) spinning film doped with potassium tantalum niobate (KTN), comprising the following specific steps: Heat a certain amount of deionized water to 80 °C, add a certain mass of polyvinyl alcohol (PVA) powder to make a 6% mass fraction polyvinyl alcohol (PVA) aqueous solution; Weigh a certain mass of potassium tantalum niobate (KTN) powder, add it to a certain amount of polyvinyl alcohol (PVA) aqueous solution, and stir magnetically for 1 h to make a polyvinyl alcohol (PVA) electrospinning solution with a potassium tantalum niobate (KTN) mass fraction of 0.4%; Use the electrospinning process to make a polyvinyl alcohol spinning film doped with potassium tantalum niobate.

[0045] In the first preparation method described above, the mass ratio of deionized water, polyvinyl alcohol (PVA), and potassium tantalum niobate (KTN) is 60:6:0.06.

[0046] In the electrospinning process, the applied voltage of the electrospinning solution is 10 kV, and the feeding rate is 0.1 mL h -1 , and the spinning distance is 10 cm.

[0047] Example 6

[0048] A preparation method of a triboelectric nanogenerator doped with potassium tantalum niobate, including a first preparation method of a polyvinyl alcohol (PVA) spinning film doped with potassium tantalum niobate (KTN), comprising the following specific steps: Heat a certain amount of deionized water to 80 °C, add a certain mass of polyvinyl alcohol (PVA) powder to make a 15% mass fraction polyvinyl alcohol (PVA) aqueous solution; Weigh a certain mass of potassium tantalum niobate (KTN) powder, add it to a certain amount of polyvinyl alcohol (PVA) aqueous solution, and stir magnetically for 1 h to make a polyvinyl alcohol (PVA) electrospinning solution with a potassium tantalum niobate (KTN) mass fraction of 1.6%; Use the electrospinning process to make a polyvinyl alcohol spinning film doped with potassium tantalum niobate.

[0049] In the first preparation method described above, the mass ratio of deionized water, polyvinyl alcohol (PVA), and potassium tantalum niobate (KTN) is 90:10:0.3.

[0050] In the electrospinning process, the applied voltage of the electrospinning solution is 20 kV, and the feeding rate is 0.3 mL h -1 , and the spinning distance is 15 cm.

[0051] Example 7

[0052] It also includes a third preparation method of potassium tantalum niobate (KTN), specifically: First, dissolve a certain mass of flaky solid potassium hydroxide (KOH) in deionized water and stir to obtain a 5 mol / L potassium hydroxide (KOH) solution. Weigh 1 g of Ta with a molar ratio of 2:3 2 O5 and Nb 2 O 5 and added to potassium hydroxide (KOH) solution to obtain a potassium hydroxide (KOH) mixed solution; 0.1 g of polyvinyl alcohol (PVA) surfactant was added to 90 g of the potassium hydroxide (KOH) mixed solution; the above-obtained mixed solution was stirred with a magnetic stirrer for 1 hour, then the mixed solution was poured into the polytetrafluoroethylene inner liner of a hydrothermal reactor and reacted at 100 °C for 10 hours; after the reaction stopped, it was allowed to cool naturally to room temperature, and the potassium tantalate niobate (KTN) precipitate was obtained by suction filtration and washing with deionized water and absolute ethanol, and then dried for 2 hours to obtain potassium tantalate niobate (KTN) powder.

[0053] In the third preparation method described above, the mass fraction ratio of potassium hydroxide (KOH) solution, Ta 2 O 5 and Nb 2 O 5 is: 90:1:0.1.

[0054] In the third preparation method described above, the particle sizes of Ta 2 O 5 and Nb 2 O 5 are about 5 μm and 1 μm respectively.

[0055] Example 8

[0056] It also includes the third preparation method of potassium tantalate niobate (KTN), specifically: First, a certain mass of flaky solid potassium hydroxide (KOH) was dissolved in deionized water and stirred to prepare a 10 mol / L potassium hydroxide (KOH) solution. Weigh 1 g of Ta with a molar ratio of 6:8 2 O 5 and Nb 2 O 5 and added to 110 g of potassium hydroxide (KOH) solution to obtain a potassium hydroxide (KOH) mixed solution; 0.5 g of polyvinyl alcohol (PVA) surfactant was added to the potassium hydroxide (KOH) mixed solution; the above-obtained mixed solution was stirred with a magnetic stirrer for 3 hours, then the mixed solution was poured into the polytetrafluoroethylene inner liner of a hydrothermal reactor and reacted at 350 °C for 20 hours; after the reaction stopped, it was allowed to cool naturally to room temperature, and the potassium tantalate niobate (KTN) precipitate was obtained by suction filtration and washing with deionized water and absolute ethanol, and then dried for 2 hours to obtain potassium tantalate niobate (KTN) powder.

[0057] In the third preparation method described above, the mass fraction ratio of potassium hydroxide (KOH) solution, Ta 2 O 5 and Nb 2 O 5The mass fraction ratio of the mixture and polyvinyl alcohol (PVA) surfactant is: 110:1:0.5.

[0058] In the third preparation method described above, Ta 2 O 5 and Nb 2 O 5 have particle sizes of approximately 10 μm and 10 μm, respectively.

[0059] It should be noted that: in the first preparation method and the third preparation method, the polyvinyl alcohol is one of polyvinyl alcohol 2699, polyvinyl alcohol 1788, polyvinyl alcohol 1799, polyvinyl alcohol 2099, and polyvinyl alcohol 2488.

Claims

1. A triboelectric nanogenerator doped with potassium tantalate niobate, characterized by: The invention comprises a friction pair positive electrode and a friction pair negative electrode. The friction pair positive electrode is made of a polyvinyl alcohol spinning film doped with potassium tantalate niobate, and the friction pair negative electrode is made of a perfluoroethylene propylene polymer.

2. The method for preparing a triboelectric nanogenerator doped with potassium tantalate niobate according to claim 1, characterized in that: A method for preparing a polyvinyl alcohol spinning membrane doped with potassium tantalate niobate comprises the following steps: firstly, dissolving polyvinyl alcohol in deionized water at 80°C, heating and stirring to obtain a polyvinyl alcohol aqueous solution; then, synthesizing potassium tantalate niobate by a hydrothermal method, adding potassium tantalate niobate to the polyvinyl alcohol aqueous solution according to a certain mass fraction to obtain an electrospinning solution, and obtaining a polyvinyl alcohol spinning membrane doped with potassium tantalate niobate by electrospinning.

3. The method for preparing a triboelectric nanogenerator doped with potassium tantalate niobate as claimed in claim 2, characterized in that: The preparation method 1 comprises the following specific steps: heating a certain amount of deionized water to 80° C., adding a certain amount of polyvinyl alcohol powder to prepare a polyvinyl alcohol aqueous solution with a mass fraction of 6% to 15%; weighing a certain amount of potassium tantalate niobate powder, adding it to a certain amount of polyvinyl alcohol aqueous solution, and magnetically stirring for 1 hour to prepare a polyvinyl alcohol spinning solution with a mass fraction of potassium tantalate niobate of 0.4% to 1.6%; The polyvinyl alcohol spinning membrane doped with potassium tantalate niobate was prepared by electrospinning process.

4. The method for preparing a triboelectric nanogenerator doped with potassium tantalate niobate as claimed in claim 3, characterized in that: In the preparation method 1, the mass ratio of deionized water, polyvinyl alcohol and potassium tantalate niobate is 60-90:6-10:0.06-0.

3.

5. The method for preparing a triboelectric nanogenerator doped with potassium tantalate niobate as claimed in claim 4, characterized in that: In the electrospinning process, the applied voltage of the electrospinning solution is 10-20 kV, and the feed rate is 0.1-0.3 mL h -1 , the spinning distance is 10 to 15 cm.

6. The method for preparing a triboelectric nanogenerator doped with potassium tantalate niobate as claimed in claim 5, characterized in that: It also includes a second preparation method for manufacturing a friction pair positive electrode and a friction pair negative electrode, which is specifically: a 5cm×5cm polyvinyl alcohol spinning membrane doped with potassium tantalate niobate is used as a friction pair positive electrode, and a 5cm×5cm perfluoroethylene propylene polymer is used as a friction pair negative electrode, and a friction nanogenerator is assembled through the friction pair positive electrode and the friction pair negative electrode.

7. The method for preparing a triboelectric nanogenerator doped with potassium tantalate niobate as claimed in claim 6, characterized in that: It also includes a preparation method three for preparing potassium tantalate niobate, which is specifically: first, a certain mass of flaky solid potassium hydroxide is dissolved in deionized water and stirred to obtain a 5-10 mol / L potassium hydroxide solution, 1g of Ta2O5 and Nb2O5 with a molar ratio of 2-6:3-8 is weighed and added to 90-110g of the potassium hydroxide solution to obtain a potassium hydroxide mixed solution; 0.1-0.5g of polyvinyl alcohol surfactant is added to the potassium hydroxide mixed solution; after stirring the mixed solution obtained above for 1-3 hours with a magnetic stirrer, the mixed solution is poured into a polytetrafluoroethylene liner of a hydrothermal reactor, and reacted at 100-350°C for 10-20 hours; after the reaction stops, it is naturally cooled to room temperature, filtered and washed with deionized water and anhydrous ethanol to obtain a potassium tantalate precipitate, and then dried for 2 hours to obtain a potassium tantalate niobate powder.

8. The method for preparing a triboelectric nanogenerator doped with potassium tantalate niobate as claimed in claim 7, characterized in that: In the third preparation method, the mass fraction ratio of potassium hydroxide solution, the mixture of Ta2O5 and Nb2O5, and the polyvinyl alcohol surfactant is: 90-110:1:0.1-0.

5.

9. The method for preparing a triboelectric nanogenerator doped with potassium tantalate niobate as claimed in claim 8, characterized in that: In the preparation method three, the particle sizes of Ta2O5 and Nb2O5 are approximately 5-10 μm and 1-10 μm, respectively.

10. The method for preparing a triboelectric nanogenerator doped with potassium tantalate niobate according to claim 9, characterized in that: In the preparation method 1 and the preparation method 3, the polyvinyl alcohol is one of polyvinyl alcohol 2699, polyvinyl alcohol 1788, polyvinyl alcohol 1799, polyvinyl alcohol 2099, and polyvinyl alcohol 2488.